2022
DOI: 10.3390/jcm11051161
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptors in the Aortic Arch and Their Potential Role in Aortic Dissection and Aneurysms

Abstract: The arterial baroreflex is a key autonomic regulator of blood pressure whose dysfunction has been related to several cardiovascular diseases. Changes in blood pressure are sensed by specific mechanosensory proteins, called baroreceptors, particularly located in the outer layer of the carotid sinus and the inner curvature of the aortic arch. The signal is propagated along the afferent nerves to the central nervous system and serves as negative feedback of the heart rate. Despite extensive research, the precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(192 reference statements)
0
5
0
Order By: Relevance
“…We examined rat aortic sections to see whether the above-mentioned alterations of BRS were related to any morphological change in the aortic arch, where baroreceptors are located [11]. Figures 5(a)–5(c) are representative photos of hematoxylin-eosin-stained sections of the aortic arch at 12.5x magnification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined rat aortic sections to see whether the above-mentioned alterations of BRS were related to any morphological change in the aortic arch, where baroreceptors are located [11]. Figures 5(a)–5(c) are representative photos of hematoxylin-eosin-stained sections of the aortic arch at 12.5x magnification.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to explore the mechanisms behind augmentation of BPV in hypertension induced by continuous infusion of Ang II. Accordingly, we examined the relationship between BP and heart rate (HR), alterations in baroreceptor reflex sensitivity (BRS), and medial area of the aortic arch where baroreceptors are located [11], following continuous infusion of Ang II over 14 days. In addition, we treated Ang II-infused rats with azelnidipine to clarify the mechanism of action of Ang II and to examine the effects of calcium channel blocker.…”
Section: Introductionmentioning
confidence: 99%
“…eNOS null mice are hypertensive, and high-pressure baroreceptors that sense blood pressure and feed back to modulate vasal tone are localised within the adventitia of the aortic arch in both the fetus and the adult. These baroreceptors are stretch receptors that sense distension of the arterial wall in response to increased blood pressure (reviewed by Reutersberg et al, 2022 ). Studies in which eNOS was reconstituted in the endothelium of adult eNOS null mice showed that although this restored vascular reactivity, the mice continued to be hypertensive ( Suvorava et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An aortic dissection can potentially cause disruption in the signal transduction of blood pressure homeostasis [12]. The stress that the aortic wall experiences during an acute dissection can stimulate the mechano-sensory baroreceptors in the outer layer of the aortic arch, which in turn, via stretch of the carotid sinus, initiates the baroreceptor response that leads to bradycardia.…”
Section: Stimulation Of the Carotid Sinusmentioning
confidence: 99%